Education in rural India - Yadav, Satish Kumar (Kurukshetra)
The Government has made good efforts by allocating funds to various programmes and schemes for the improvement of quality of schools and higher education. But still there is need to improve the investment allocated under different schemes of education with a focus on education of rural India. - Reproduced
Keywords: Rural development - India, Primary education - India